SENI DALAM PANDANGAN ALQURAN - Yedi Purwanto (Fakultas Seni Rupa dan Desain ITB, 2010)
The Qur'an is a holly book (kitabullah) revealed to Prophet Muhammad. One of al-qur'an functions is as a guide or guidance for mankind, which details God's other holly books. (Qur'an: 2:185). One form of al-qur'an guidance is about art. Al-qur'an globally discusses art, whether painting art, painting, and other arts. One of Allah